Rapidly spreading deep dissecting hematoma occurring 1 month after a minor trauma: A case report. (November 2022) - Hamdan, Rémy; Zwetyenga, Narcisse; Macheboeuf, Yvan; Ray, Patrick
A deep dissecting hematoma is the most serious complication of dermatoporosis, consisting of a rapidly expanding blood collection that splits the hypodermis from the muscle fascia. A several-week time lapse between a minor trauma-induced superficial hematoma and its sudden evolution into a rapidly spreading deep dissecting hematoma is unusual. We report the case of a 70-year-old woman with long-term oral anticoagulation and dermatoporosis who suddenly developed a rapidly spreading right-leg deep dissecting hematoma 1 month after minor trauma, for which a surgical debridement and drainage were performed. Only local care and absorbent dressings were used to manage the post-operative wound, and within 4 months, the wound had healed. In this report, we emphasize the importance of preventing deep dissecting hematoma in patients who are at risk as well as the need to weigh the benefits and risks of anticoagulants when dermatoporosis cutaneous signs are present. A limb-threatening deep dissecting hematoma may develop suddenly, even weeks after a minor impact. In order to prevent skin necrosis from occurring, caregivers, patients, and carers must be able to identify this condition early on.